1994
DOI: 10.1111/j.1540-4560.1994.tb02424.x
|View full text |Cite
|
Sign up to set email alerts
|

From Knowledge to Action? Exploring the Relationships Between Environmental Experiences, Learning, and Behavior

Abstract: On the basis of qualitative research and two surveys with 786 and 1004 Swiss respondents, this article presents a new “life‐world” approach to exploring the complex relationships between environmental experience, learning, and behavior. Contrary to traditional views, the author shows that environmental information, knowledge, and awareness predict little of the variability in most forms of environmental behavior. (The primary behaviors that information and knowledge acquisition appear to foster are protest act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(129 citation statements)
references
References 7 publications
5
119
1
4
Order By: Relevance
“…More importantly, nature experiences are considered the basis for environmental awareness which leads to pro-environmental consumer behavior [13,15]. That is, nature experiences are an important factor that drives eco-friendly behavior [51]. Bögeholz [50] also suggested that people who have a higher level of nature experiences tend to develop an awareness of protecting nature, so they are more likely to display environmentally friendly behaviors.…”
Section: Nature Experiencesmentioning
confidence: 99%
“…More importantly, nature experiences are considered the basis for environmental awareness which leads to pro-environmental consumer behavior [13,15]. That is, nature experiences are an important factor that drives eco-friendly behavior [51]. Bögeholz [50] also suggested that people who have a higher level of nature experiences tend to develop an awareness of protecting nature, so they are more likely to display environmentally friendly behaviors.…”
Section: Nature Experiencesmentioning
confidence: 99%
“…For example, Palmer's (1999) research with 1259 students in nine countries including Australia found that direct experiences with nature had far more impact on subsequent involvement in pro-environmental activities than did formal education. Similarly, Finger (1994) found nature experiences to be a better predictor of environmental behaviour than environmental awareness, information, or value orientations. Dettmann-Easler and Pease's (1999) review of research suggests that environmental education that is solely school-based is only moderately successful, and that the best approach for teaching environmental concepts and awareness is to incorporate outdoor activities.…”
Section: Introductionmentioning
confidence: 99%
“…Li (1997) showed that feelings towards the environment are substantially related to affective behaviors and that knowledge does not seem to be an antecessor of emotions. Finger (1994) had also demonstrated that the experiences with the nature are powerful instigators of pro-environmental behaviors, showing that these experiences are still more important than the explanation on their functioning. In this manner, the emotional affinity with the nature may be different from the cognitive interest in its parts, or from the curiosity on the flora, fauna, and the variety of its phenomena and natural processes.…”
Section: Discussionmentioning
confidence: 99%